Extensão comunitária: analisando alternativas e desafios para o aprofundamento da participação da comunidade na gestão de projetos de extensão popular da UFPB - Bernardo, Klebson Felismino (2022)
This research is supported by the main idea of Community Extension (EC) and guided by the theoretical methodological principles of Popular Education (PE). In the context of this study, CE is understo od as the movement in which the community, in its dialogue with popular extension projects, interacts with the university in a protagonist way, either in the production of knowledge that is being developed in the academy, or in the management and in the de velopment of extension activities. Thus, CE would involve, in its definition, the possibility of making an “extension” from the outside (community) to the inside (university), with the active participation of the community and its protagonists in processes and experiences in the university environment. Based on this idea force, the study on screen was developed with community members and coordinators of different popular extension projects at the Federal University of Paraíba (UFPB). Its general objective w as to understand how UFPB's popular extension projects have considered and promoted the participation of the community, its local subjects in the management of these projects, and in other dimensions of university life, based on the conception community ou treach. In methodological terms, the research is anchored in the methodological principles of the qualitative perspective, of an exploratory nature, through bibliographic research and semi structured interviews. Regarding the theory of analysis, the study adopted the hermeneutic dialectic, based on the contributions of Jürgen Habermas (1987) and Hans Georg Gadamer (1999). The development of the research contemplated the delimitation of the historical context of the university extension, the explanation of t he political pedagogical reference of the EP, and the in depth presentation of the Popular Extension; its theoretical methodological aspects, potentialities and exchange with popular sectors. The idea of CE, its dimension of polysemic conception and the main uses and interpretations of it in the light of current literature were placed. Extension experiences based on EC were also presented. The results indicate that it is necessary to expand the theoretical production on the idea of CE, in view of the ti mid exploration of this category in the current literature. The interviewees highlighted the potential of this conception, in the perspective of the relevance of considering popular participation as a basic element of popular extension, of the perspectives of densification of the university and its social impact. It was also highlighted that the CE can break the distances between university and society, as well as increase the spaces in which the coordinators, students and technicians of the extension proje cts can listen to the demands of the community, with a view to also strengthening the dialogue. horizontalized between subjects and contexts. The study pointed, through the experiences and perceptions of the interviewees, aspects related to the involvement of community actors with the extension projects; the constitution of the coordinators' relationship with the community and the challenges to be faced; issues related to project management and the perspective of participatory and dialogic management of the same. It is understood that this idea, deepened from a theoretical and methodological point of view, can provide more possibilities to support popular extension projects to stimulate and promote the involvement of the community and its subjects in the uni versity context. In summary, EC can contribute to the historical movement that popular extension practices have been developing in the university field, by pointing out theoretical and methodological aspects that qualify their practices and contribute to t he advancement of academic initiatives guided by critical, respectful and purposeful dialogue of knowledge (scientific and popular) Furthermore, it can broaden the epistemic horizon and make the university permeated also by knowledge and experiences, based on the concrete reality of different popular social subjects.